Dormancy overcome and seedling quality of pecan in nursery - Tales Poletto; Marlove Fátima Brião Muniz; Igor Poletto; Valdir Marcos Stefenon; Caciara Gonzatto Maciel; Jéssica Emilia Rabusque (Ciência Rural)
ABSTRACT: This study evaluated the efficiency of methods to overcome seed dormancy in different storage periods in the production of pecan seedlings. Seeds were submitted to the following treatments: T1, T4 and T7 - control treatments (seeds with no treatment, stored at room temperature for 30, 60 and 90 days, respectively), T2, T5 and T8 - stratification (seeds were distributed in boxes with wet sand maintained at a temperature of 4°C for 30, 60 and 90 days, respectively), T3, T6 and T9 - scarification + stratification (seeds scarified with sandpaper n.80 and stratified by 30, 60 and 90 days, respectively), in completely random experimental design. Plant height, stem diameter, number of leaves, full emergence and emergence speed index (ESI) were evaluated after 14 weeks of sowing. The best development of pecan 'plants, their emergence, and ESI were observed in the stratification treatment for 90 day as well as in the scarification + stratification treatment for 90 day. Storing seeds in uncontrolled environment reduced their viability.